Competition law and regulations: Productivity impacts in Latin American manufacturing firms - Sara A. Wong; Marjan Petreski (Inter-American Development Bank (IDB), 2025)
This paper investigates the effects of competition laws and regulations on manufacturing firms productivity in Latin American countries (LACs), addressing a gap in existing research. Leveraging firm-level panel data from the World Bank Enterprise Surveys across 14 LAC economies and competition law indicators from the Comparative Competition Law initiative, the study employs total factor productivity (TFP) measures to analyze the effects of competition laws on manufacturing productivity through key mediators: firm size, distance to the frontier, and broader institutional arrangements. Utilizing various empirical methodologies that address potential biases, the findings reveal a nuanced relationship between competition law stringency, enforcement practices, and productivity outcomes across different industries and countries. Results reveal heterogeneous effects of competition law and enforcement on productivity, with certain aspects showing a positive relationship with productivity, particularly when controlling for firm size, while stronger enforcement measures weaken the positive association between competition law and productivity, potentially due to increased compliance costs and legal uncertainty. The study suggests a need for policymakers to strike a balance between regulatory stringency and enforcement in competition to avoid stifling innovation and hindering productivity growth, particularly in industries nearing technological frontiers. Accounting for industry-specific factors are essential for fostering fair competition and market efficiency without unduly burdening businesses.
Keywords: K21; L11; O54; 330; Competition law and regulations; Firm productivity; Enforcement; LAC